Type-II superlattice detectors for free space optics applications and higher operating temperature conditions - Hackiewicz, K.; Martyniuk, Piotr; Rutkowski, Jarosław; Manyk, Tetiana; Mikołajczyk, J. (Opto-Electronics Review, 2018)
The utmost limit performance of interband cascade detectors optimized for the longwave range of infrared radiation is investigated in this work. Currently, materials from the III–V group are characterized by short carrier lifetimes limited by Shockley-Read-Hall generation and recombination processes. The maximum carrier lifetime values reported at 77 K for the type-II superlattices InAs/GaSb and InAs/InAsSb in a longwave range correspond to ∼200 and ∼400 ns. We estimated theoretical detectivity of interband cascade detectors assuming above carrier lifetimes and a value of ∼1–50 μs reported for a well-known HgCdTe material. It has been shown that for room temperature the limit value of detctivity is of ∼3–4×1010 cmHz1/2/W for the optimized detector operating at the wavelength range ∼10 μm could be reached.